Comparison of Airflow Velocity Distribution at the Inlet in Single and Dual Inlet Cabinet Dryer: A CFD Study - Angga Darma Prabowo (INSTEP Network, 2025)
This study explores how airflow velocity is distributed in cabinet dryers with single and dual inlet systems, using Computational Fluid Dynamics (CFD) simulations. The goal was to compare how different inlet configurations affect airflow uniformity and drying performance across various rack levels. We tested four dual inlet setups with varying mass flow ratios (50%/50%, 40%/60%, 30%/70%, and 20%/80%) and compared them to a single inlet system. The results show that the single inlet configuration creates uneven airflow, with higher velocities at the top racks and lower velocities at the bottom, leading to inconsistent drying. On the other hand, dual inlet systems provide more even airflow, with the 50%/50% configuration being the most balanced. Even the more uneven dual inlet setups (such as the 20%/80% ratio) still performed better than the single inlet in terms of airflow consistency and drying efficiency. Overall, dual inlet systems, especially those with balanced airflow, enhance drying efficiency by ensuring more uniform airflow throughout the dryer. Further research could focus on optimizing these dual inlet systems for even better performance.